Analisis Kapasitas Saluran Primer Daerah Aliran Sungai (DAS) Klandasan Kecil Kota Balikpapan - Rossana Margaret Kadar Yanti (Universitas Quality, 2020)
Balikpapan City one of the developed cities in Indonesia. This condition causes problems such as flooding. Aspects relating to flooding in cities are watersheds. The study site is located in the Klandasan Kecil River Basin. Factors causing flooding in the watershed include land cover conditions that can only absorb runoff by 26.90% so that it affects the amount of runoff that occurs. Another factor is the inadequate river conditions that are unable to drain runoff discharge in the watershed. Based on the existing problems, an evaluation of the performance of the Klandasan Kecil River Basin drainage system is carried out. The evaluation was carried out by conducting a hydrological analysis on the klandasan kecil watershed and hydraulics analysis of the primary river, klandasan kecil river using the Hecras application. The results of the analysis obtained the magnitude of hydrological discharge in the Klandasan kecil watershed that is equal to 53.044 m3/s. The existing river capacity that has been analyzed using the HECRAS application on klandasan kecil river there are 10 river points whose capacity does not meet so that flooding. The height of the flood that occurred varied from 0.30 meters to 4.42 meters above the river.